First record of Ripersiella kelloggi Ehrhon and Cockerell (Hemiptera: Rhizoecidae) for the Neotropics, with a redescription of the adult female - Ramos Portilla, Andrea Amalia; Caballero, Alejandro; Kondo, Takumasa; Serna, Francisco (FLVC Library Services., 2025)
Ripersiella kelloggi Ehrhon and Cockerell (Hemiptera: Rhizoecidae) is herein reported from Colombia and the Neotropical region for the fi rst time. The species is redescribed and illustrated. The cephalic plate and genitalia of R. kelloggi are herein described for the fi rst time.